Determination and formation of Ethyl Carbamate in Chinese spirits. (October 2015) - Li, Guohui; Zhong, Qiding; Wang, Daobing; Zhang, Xinyang; Gao, Hongbo; Shen, Shigang
Abstract: This study aims to develop HPLC-FLD method and verify its applicability for Ethyl Carbamate (EC) determination in Chinese spirits, and to investigate the mechanism for EC generation and its influencing factors. HPLC-FLD with prior derivatization with 9-xanthydrol was used for the EC detection. Optimal reaction condition and the parameters usually tested in the method validation were identified and evaluated. Most appropriate mobile phase is sodium acetate solution with pH value at 7.2. Optimal alcohol strength and reaction time for derivatization are 38–42% and 50 min respectively. Good linearity was obtained with correlation coefficient greater than 0.9998; limit of detection and quantitation were 1.82 and 5.34 μg/L; recovery rate was 96.67% (±6.59%), and method precision was less than 5% (RSD). No significant difference was found in EC determination measured by HPLC-FLD and GC/MS (p > 0.05) indicating HPLC-FLD may be a suitable alternative to GC/MS with greater convenience and lower cost. The average EC content in the Chinese spirit was 39.3 μg/L (ND. to 79.1 μg/L, n = 90), and EC was mainly produced during storage. Raw material profile, brewing time, and storage time and temperature were suggested as main factors influencing EC content; moreover, lowering the storage temperature can effectively reduce EC production. Hydrocyanic acid was concluded as the EC precursor in Chinese spirits. A preliminary multiple regression model based on the storage temperature and time was produced to forecast the EC content in Chinese spirits, and this could be further developed in future research including more influencing factors. Highlights: A rapid and lowcost method for determination of EC in Chinese spirits was developed. Effects of storage time and temperature on Chinese spirits EC level were analyzed. A preliminary forecast model was established for EC content in Chinese liquor. Recommendations for reducing EC production in Chinese liquor were provided. Hydrocyanic acid was suggested as the main precursor of EC in Chinese spirits.